2001
DOI: 10.1021/ac0012041
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Nanosensors for Intracellular Chemical Analysis:  Decyl Methacrylate Liquid Polymer Matrix and Ion-Exchange-Based Potassium PEBBLE Sensors with Real-Time Application to Viable Rat C6 Glioma Cells

Abstract: Fluorescent spherical nanosensors, or PEBBLEs (probes encapsulated by biologically localized embedding), in the 500 nm-1 microm size range have been developed using decyl methacrylate as a matrix. A general scheme for the polymerization and introduction of sensing components creates a matrix that allows for the utilization of the highly selective ionophores used in poly(vinyl chloride) and decyl methacrylate ion-selective electrodes. We have applied these optically silent ionophores to fluorescence-based sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
143
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(146 citation statements)
references
References 31 publications
0
143
0
Order By: Relevance
“…[18,19] Nanospheres composed of F127 and DOS are newly introduced research tools that have not yet been applied in intracellular analysis.…”
Section: Nanosphere Uptake By Dictyostelium Discoideummentioning
confidence: 99%
“…[18,19] Nanospheres composed of F127 and DOS are newly introduced research tools that have not yet been applied in intracellular analysis.…”
Section: Nanosphere Uptake By Dictyostelium Discoideummentioning
confidence: 99%
“…Moreover, there are few biosensors developed for GBM, usually for cellular sensing (Beljebbar et al, 2010;Brasuel et al, 2001;Chen et al, 2008;Desai et al, 2006;Manning et al, 1998;Trevin et al, 1998;Valero et al, 2010;Zakir Hossain et al, 2007). The objective of the present research regards the analysis of protein-drug and multiple protein-drug interaction towards potentially useful clinical applications, namely in the field of cancer studies.…”
Section: Tmz (Brand Namementioning
confidence: 99%
“…16 More recently, spherical optical nanosensors or PEBBLEs (probes encapsulated by biologically localized embedding) with 20 -200 nm in diameter have been introduced by Kopelman for intracellular measurements of pH, calcium, potassium, chloride and glucose. [23][24][25][26] In this case, a fluorescent indicator was incorporated into the pores of a hydrophilic polymer matrix for pH and glucose sensing. 23,24 The same group has also explored the development of nanosensors based on PVC particles containing a lipophilic fluorescence indicator for intracellular electrolyte monitoring.…”
Section: Structural Design Of a Sliver Sensor For Monitoring Ph Potamentioning
confidence: 99%
“…[23][24][25][26] In this case, a fluorescent indicator was incorporated into the pores of a hydrophilic polymer matrix for pH and glucose sensing. 23,24 The same group has also explored the development of nanosensors based on PVC particles containing a lipophilic fluorescence indicator for intracellular electrolyte monitoring. 25,26 Coté et al reported hydrogel microspheres incorporating a fluorescence labeled protein for glucose monitoring, which they proposed as implantable transdermal glucose biosensors.…”
Section: Structural Design Of a Sliver Sensor For Monitoring Ph Potamentioning
confidence: 99%